PENGARUH TINGKAT KEPATUHAN DALAM MEMBAYAR WAJIB PAJAK PENGHASILAN TERHADAP SUBJEK, DAN OBJEK PPH - Chindy Jihan Najiyah; Satria Budi, Yuliana, Dini Vientiany (CV. ADIBA AISHA AMIRA, 2024)
This research aims to evaluate the impact of taxpayer awareness, tax activities, and motivation in paying taxes on total tax revenues. Even though income tax has great potential as a source of state revenue, its implementation is still limited in Indonesia. In contrast to many other countries where income tax is the backbone of tax revenues, in Indonesia, its potential has not been fully exploited. In the context of state economics and finance, loss of potential tax revenue or a decrease in tax revenue is known as tax leakage. Tax is imposed on various types of income such as fixed salaries, monthly pensions, temporary jobs, internships, potential employees, as well as MLM/direct selling distributors and similar activities, at rates determined based on Taxable Income (PKP). Income taxes can reduce incentives to invest if the amount of the tax reduces the profitability of the investment. In an income tax with proportional rates, the opportunity to make a profit or suffer a loss will be reduced equally. The results of the research show that tax sanctions and service quality from the tax authorities influence the level of taxpayer compliance, while taxpayer awareness does not have a significant impact on the level of compliance. Factors such as tax sanctions, taxpayer awareness, and the level of taxpayer compliance influence the amount of income tax revenue. However, the services provided by the tax authorities have not been proven to influence the amount of income tax revenue. Taxpayer compliance can act as a link between the services provided by the tax authorities and income tax revenues, but is unable to bridge the influence of tax sanctions and taxpayer awareness on income tax revenues